Cytoprotective and antiinflammatory effect of polyphenolic fraction from Red cabbage (Brassica oleracea Linn var. capitata f rubra) in experimentally induced ulcerative colitis - Pramod Chandrasenan, V M Anjumol, M V Neethu, Raj Selvaraj, Vysakh Anandan, Gikku Martin Jacob (Journal of Applied Pharmaceutical Science, 2016)
In present study we investigated the anti-inflammatory effect of polyphenolic fraction isolated from Red cabbage Brassica oleracea Linn var. capitata f. rubra (PBO) on lipoplysacharide (LPS) stimulated HT-29 colonocytes and in rats with acetic acid induced colitis. Our results from in vitro studies demonstrated that PBO effectively attenuated the inflammatory response produced by cycloxygenase (COX), 5-lipoxygenase (5-LOX) and oxidative stress created via reactive oxygen species (ROS) and nitric oxide (NO) in LPS treated HT-29 cells. Additionally PBO down regulated the mRNA expression of inflammatory marker genes like COX-2, inducible nitric oxide (iNOS) tumor necrosis factor α (TNF-α), interleukin-6 (IL-6) in HT-29 cells. PBO at a dose of 200 mg/kg body weight was tested in treatment groups of animals (n = 6) for 14 consecutive days after induction of colitis. The colonic mucosal injury was assessed by histological examination. Moreover, PBO administration markedly increased the mucin content as evidenced in periodic acid Schiff (PAS) staining and the mucosal content of lipid peroxidation (LPO), confirms that PBO could significantly inhibit colonic mucosal damage. These results indicated that PBO exert marked anti-inflammatory effect in experimental colitis, possibly by regulating the antioxidant and inflammatory mediators.
Keywords: Polyphenol,Red cabbage,Colitis,Anti-inflammatory,Cycloxygenase,Antioxidant.